Resistance against Bacillus thuringiensis endotoxins in a laboratory population of Helicoverpa armigera is based on an elevated immune status - Muhammad Sarjan; Mahbub M Rahman; Gang Ma; Otto Schmit (Jurnal ILMU DASAR, 2009)
Recent   observations   suggest   that   lectin-like   toxins,   such   as   endotoxins   from  Bacillus   thuringiensis  are sequestered inside the gut of immune-induced insects providing tolerance to Bt-formulations. To investigate the induction   and   sequestration   process,   we   used   toxin   and   lectins   that   bind   to   galactosamine   (Gal)   and   N-acetylagalactosamine (GalNAc) to identify binding sites in the midgut of induced and non-induced insects using confocal   microscopy.   Our   observations   suggest   that   immune   and   metabolic   hemolymph   components   are transported across the gut epithelium and accumulate inside the gut lumen in Bt-tolerant insects. Co-location of immune components and toxin indicates that some of the toxin is inactivated by coagulation reactions inside the gut lumen before it can reach the brush border membrane